(untitled) (PerCursos, 2022)
The permanence and popularization of the Earth’s memory for the citizen and human formation of current and future generations, through the constitution and conservation of natural heritage, built over millions of years through constant terrestrial dynamics and endogenous and exogenous processes associated with them, they are essential. In this context, the objective of this manuscript is to analyze the concept of Geoheritage, through the (re)construction of the mater concept of heritage and the discussion of forms and spaces of applicability. The methodological script developed has a qualitative approach, compartmentalized in a theoretical-conceptual basis, centered on Geoheritage and related areas, and in a technical-scientific contingent, subdivided into interrelated stages of cabinet (surveys and analysis of materials), field (primary data collection and empirical analysis) and laboratory (preparation of non-textual materials – charts and maps). Rescue and understand the approach in the academic environment and its application with civil society of this important, but still not very widespread, concept of geosciences, presents itself as something significant and relevant. And it is in this sense that this work seeks to advance studies and initiatives aimed at geoheritage, to contribute to discussions about the concept, methodological approaches and their possible applications.